Study on the implementation of the Internet of Things in the sustainable agricultural revolution from upstream to downstream - Widharma, I Gede Suputra; Sumadi , Ketut; Anggreni , Anak Agung Made Dewi (C-DISC, 2024)
This study employs a review-based methodology to explore the utilization of Internet of Things (IoT) technology within the agricultural industrial revolution, encompassing processes from upstream to downstream. IoT technology plays a pivotal role in accelerating the adoption of regenerative agriculture principles by enabling the integration of sensors, communication devices, and digital platforms into a unified system. This system facilitates the monitoring and optimization of sustainable agricultural practices, covering stages from planting to the distribution of agricultural products. The bidirectional digital communication established between human-to-system and system-to-human interactions ensures seamless information exchange. The research introduces a conceptual framework for smart regenerative agriculture, comprising smart farming (upstream), smart harvesting and packing, and smart marketing (downstream). By leveraging IoT technology, this framework aims to create an agricultural system that is not only more efficient and environmentally sustainable but also capable of addressing the challenges of national food security. Furthermore, the study examines various case studies of IoT implementation in other countries, providing valuable insights and benchmarks for its potential application in Indonesia.